Impact of agricultural credit on productivity, cost and returns from cocoa production in Ghana - Boansi, David; Gyasi, Michael; Nuamah, Stephen; Tham-Agyekum, Enoch Kwame; Anyuki, Fred; Frimpong, Richmond; Gbafah, Albert; Gyan, Charles Bosompem (Informa UK Limited, 2024)
This study identified the determinants of cocoa farmers’ access to credit in Ghana and estimated the impact of credit access on yield, yield gap, gross income, cost of production, and net income using propensity score matching. A total of 384 cocoa-farming households were included in the analysis. Only 33.3% of cocoa farmers accessed credit for production and cooperative unions were the main source of credit accessed by the farmers. The study finds significant positive impacts of agricultural credit on yield, gross income, and net income, while yield gap decreases significantly (by 12.2–16.7%) with access to credit. Policy efforts to improve cocoa farmers’ access to credit could therefore enhance the productivity and profitability of cocoa production. It was found that male-headed households with access to credit derive greater benefits than their female counterparts. This may be attributed to differences in resource endowments and marginalization (between male and female heads). In addition, it was found that with access to credit, cultivating more than one cocoa farm could make cocoa production more productive and profitable. This indicates more efficient and profitable use of credit on fragmented farms, than on non-fragmented farms. However, under credit constraint, the practice of land fragmentation could be counterproductive.